A Bad Case of Electronic-Word-of-Mouth : A Bachelor Thesis on Negative EWOM and its Effects on Consumer Purchase Intentions and Brand Attitude - Klingstedt, Johan; Naderi, Sandra (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2020)
Background: The expansion of the World Wide Web has presented new challenges for managers. One of these challenges is the shift in power that favors consumers through the uprising of electronic word of mouth (eWOM). This thesis is aimed to the exploration of the effects on consumer purchase intention and brand attitude because of an unsuccessful marketing campaign. Methodology: Interviews have been conducted with a central theme of a case study of Pepsi to gain knowledge on the effects a marketing failure and exposure to eWOM has on students at Luleå University of Technology. Findings: EWOM is indicated to influence consumers’ intention of purchase as well as the attitude for the brand. EWOM is indicated to be influenced by the response to the advertisement in a negative context and may influence consumers to actively share their opinions to others through an electronic medium, thus contributing to the spread of eWOM. The attitude of the brand is indicated to influence the effects of negative eWOM, being of more influence when the brand attitude is bad. Conclusions: Managers and business practitioners need to be aware of the power of eWOM and its effects on purchase intention and brand attitude and should respond quickly to any unwanted spread of negative thoughts regarding the company before it is too late. Research question: How is consumer brand attitude and purchase intention affected by negative eWOM in the context of an unsuccessful online marketing campaigns? Purpose: The purpose of this study is to explore the potential change in customer attitudes and purchase intentions because of negative eWOM communication regarding unsuccessful marketing campaigns